Educational Webinar: Making Paraphrase Easier For Those Who Have Already Copy Pasted: Webinar Edukatif: Memudahkan Parafrase Bagi Yang Terlanjur Copy Paste - Salman, Salman; Hasanah, Uswatun; Handayani, Dila; Indriana, Meutia; Muzakkir, Muzakkir (Universitas Haji Sumatera Utara, 2025)
The high prevalence of plagiarism in the creation of scientific articles and the widespread practice of copy-pasting underpin the motivation for this activity. The purpose of this initiative is to provide a solution to the recurring issue of plagiarism resulting from such practices. Additionally, the activity aims to offer insights and skills to participants in avoiding acts of plagiarism. The methodology employed involves interactive discussions and live demonstrations conducted online through the Zoom application, packaged in the form of a webinar. This Community Engagement project was attended by 33 participants, consisting of lecturers and senior university students from Tjut Nyak Dhien University .The findings from this initiative revealed an enhancement in participants' understanding of paraphrasing practices and the negative impacts of plagiarism. Furthermore, participants acquired practical skills in effectively applying paraphrasing techniques, resulting in a better comprehension of the significance of creating original content and how to avoid plagiarism. In conclusion, the webinar provided a comprehensive perspective on the importance of plagiarism prevention, enhancing awareness of potential legal and academic consequences associated with such actions.